2013
DOI: 10.3390/ijms140918009
|View full text |Cite
|
Sign up to set email alerts
|

Celf1 Is Required for Formation of Endoderm-Derived Organs in Zebrafish

Abstract: We recently reported that an RNA binding protein called Cugbp Elav-like family member 1 (Celf1) regulates somite symmetry and left-right patterning in zebrafish. In this report, we show additional roles of Celf1 in zebrafish organogenesis. When celf1 is knocked down by using an antisense morpholino oligonucleotides (MO), liver buds fail to form, and pancreas buds do not form a cluster, suggesting earlier defects in endoderm organogenesis. As expected, we found failures in endoderm cell growth and migration dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…We find that knockdown of Celf1 results in cardiac looping defects and other morphological defects in the embryonic Xenopus heart as well, suggesting that the involvement of Celf1 in this process is evolutionarily conserved. Although Celf1 is not expressed in endoderm‐derived organs in zebrafish, depletion of Celf1 in zebrafish embryos affects not only mesoderm‐derived tissues, but also leads to defects of endoderm‐derived organs such as liver and pancreas, including failure of gut looping (Tahara et al, ). In our study in the developing Xenopus embryo, we also observe gut morphological abnormalities following knockdown of Celf1, but have not further investigated this phenotype.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We find that knockdown of Celf1 results in cardiac looping defects and other morphological defects in the embryonic Xenopus heart as well, suggesting that the involvement of Celf1 in this process is evolutionarily conserved. Although Celf1 is not expressed in endoderm‐derived organs in zebrafish, depletion of Celf1 in zebrafish embryos affects not only mesoderm‐derived tissues, but also leads to defects of endoderm‐derived organs such as liver and pancreas, including failure of gut looping (Tahara et al, ). In our study in the developing Xenopus embryo, we also observe gut morphological abnormalities following knockdown of Celf1, but have not further investigated this phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, CELF1 undergoes a pronounced decline postnatally (Kalsotra et al, ) that is concomitant with the hyperplastic‐to‐hypertrophic transition. Knockdown of Celf1 was also shown to lead to reduced proliferation in endodermal cells during zebrafish embryonic development (Tahara et al, ), and competition between CELF1 and calreticulin has been suggested to drive a biological switch between senescence and proliferation in hepatocytes and fibroblasts (Iakova et al, ; Timchenko et al, ; Barreau et al, ). Together, these data suggest a role for CELF1 in the regulation, directly or indirectly, of proliferation in multiple germ layers.…”
Section: Discussionmentioning
confidence: 99%
“…Another study has also showed a link between Cdc42 and p120 Catenin signaling during gastrulation [6]. Moreover, it has been shown that Celf1 (CUGBP Elav-like family member 1), a RNA binding protein, binds several mRNAs including cdc42, to control zebrafish somite symmetry, left-right patterning and endoderm organogenesis [59]. Cdc42 is therefore required during early zebrafish morphogenetic events in mesodermal and endodermal cells.…”
Section: Cdc42 In Cell Movement and Rearrangementmentioning
confidence: 99%
“…Zeb cdc42-F 5 -GACAGTAGCCCTGTAAATGGTTG-3 [59] Zeb cdc42-R 5 -GTTAGAAAGTTCCCTGCTTGAGAG-3 [59] RhoA qrhoaa_F TCCTGAGGTTTACGTTCCCA [49] qrhoaa_R TGGCCAGCTGTATCCCATAG [49] qrhoab_F ACAGGCTTCGTCCTCTTTCA [49] qrhoab_R AATGTTTGACCTCAGGCGTC [49] 6. Conclusions…”
Section: Cdc42mentioning
confidence: 99%
“…[ 8 , 9 ]. CELF1 is involved in many body homeostasis such as development of embryonic and heart, differentiation of bone and adipose tissue, as well as formation germ cells [ 10 12 ]. The aberrant expression of CELF1 leads to multiple diseases such as myotonic dystrophy type 1 (DM1) [ 13 ], myocardial hypertrophy [ 14 ].…”
Section: Introductionmentioning
confidence: 99%